What is participatory democracy and how can it be developed in the classroom? - Spajić-Vrkaš, Vedrana (2011)
Participation of citizens at different levels in decision making is the pillar of a healthy or, as Barber calls it, a strong democracy. Active participation is learned through participation. However, not all participatory activities in school lead to participative citizenry. In many instances students are manipulated and tokenized. A true learning for participation presupposes power-sharing between students and teachers with a view to built students' capacity and self-reliance, which could be achieved through citizenship education focused on students' empowerment.